Das Problem der Altlastenentdeckung - Anreize zur Informationsenthüllung durch eine Kronzeugenregelung? - Roswitha Kleineidam; Markus Lehmann (Max-Planck-Projektgruppe Recht der Gemeinschaftsgüter, 2000)
– The paper argues that the existing German and American liability rules for the cleanup of Superfund sites do not generate incentives to reveal private information on the existence of a contaminated site. It presents a infinite-horizon dynamic model of imperfect information and shows that such incentives are generated by appropriately reducing the liability share of any potentially responsible party which reveals its private information. The necessary reduction is a function of the probability of exogenous discovery and of the discount factor of the potentially responsible party. By referring to the legal literature on State's evidence, the paper analyses the problems related with different possibilities of designing the reduction rule.
Keywords: 340